Full pseudocapacitive behavior hypoxic graphene for ultrafast and ultrastable sodium storage. Issue 19 (11th May 2020) - Wang, Ying-Ying; Hou, Bao-Hua; Yang, Xu; Chen, Dong; Liang, Hao-Jie; Gu, Zhen-Yi; Rui, Xian-Hong; Wu, Xing-Long
Abstract : A hypoxic graphene with full pseudocapacitive behavior is successfully prepared and exhibits super fast-charging/discharging performance and ultralong lifespan for Na-storage. Abstract : Achieving fast-charging/discharging (FCD) performance for sodium-ion batteries (SIBs) has always been a great challenge, because of their slow reaction kinetics and the difficulty in ensuring the stability of the electrode during sodiation/desodiation. In this study, a hypoxic graphene (HG) is rationally designed and prepared using a simple high temperature treatment process. It is confirmed that the hypoxic surface is more conducive to the rapid conduction of electrons and forming a high quality SEI film in the first cycle to avoid irreversible side reactions. Furthermore, a versatile electrolyte suitable for improving the FCD performance of different carbon materials is screened and used in this system. As a result, the best sample of HG-1300 shows almost full pseudocapacitive behavior as an anode material for SIBs, and exhibits a super FCD performance (110 mA h g −1 at an ultrahigh current density of 200 A g −1, only 4 seconds per cycle) and ultralong lifespan (90.7% capacity retention over 100 000 cycles at 20 A g −1 ), even surpassing supercapacitors.